Plant extracts as biostimulants of growth, yield and quality of fruit in bell pepper - Jasso-Cantú, Diana; Rocha-Rivera, Martín Francisco; Ramírez-Rodríguez, Homero; Villarreal-Quintanilla, José Ángel; Díaz-Jiménez, María Lourdes Virginia; Rodríguez-García, Raúl; Carrillo Lomelí, Dennise Anahí (Ecosistemas y Recursos Agropecuarios, 2023)
The objective of this study was to evaluate the effect of four methanolic plant extracts from the Northeast Mexican Semidesert: Rhus muelleri, R. virens, Flourensia microphylla and F. retinophylla, as biostimulants for growth, yield and fruit quality in bell pepper; compared with the bioregulators gibberellic acid, indoleacetic acid and 6-benzylaminopurine. The dose utilized of extracts and bioregulators was 75 mg L−1, applying them at transplant and, at 33 and 46 days after transplant (DAT). Besides, the extracts were also applied at 17 and 96 DAT. The evaluated variables in plants were longitudinal growth and stem diameter, total dry matter, root length and volume, number of fruits and yield. In fruits were evaluated weight, longitudinal and equatorial diameters, volume, firmness, titratable acidity, total soluble solids (TSS), total phenolic content, anthocyanins, lycopene and vitamin C; as well as dry weight of seeds. The experiment was established under a completely randomized design with eight treatments and 12 repetitions. The F. retinophylla extract promoted higher fruit weight per plant (212.9 g), fruit volume (404.2 cm3) and yield (1.57 kg plant−1). Moreover, in fruits were observed increments on vitamin C content (100.1 mg 100 g−1) and TSS (8.6 °Brix) with F. microphylla and R. muelleri, respectively. These results were statistically equals or superior to those of bioregulators. In general, the extracts promoted a higher growth, yield and fruit quality of bell pepper var. Cannon, than the bioregulators.